2008
DOI: 10.1172/jci35808
|View full text |Cite
|
Sign up to set email alerts
|

Lnk controls mouse hematopoietic stem cell self-renewal and quiescence through direct interactions with JAK2

Abstract: In addition to its role in megakaryocyte production, signaling initiated by thrombopoietin (TPO) activation of its receptor, myeloproliferative leukemia virus protooncogene (c-Mpl, or Mpl), controls HSC homeostasis and self-renewal. Under steady-state conditions, mice lacking the inhibitory adaptor protein Lnk harbor an expanded HSC pool with enhanced self-renewal. We found that HSCs from Lnk -/-mice have an increased quiescent fraction, decelerated cell cycle kinetics, and enhanced resistance to repeat treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
232
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(261 citation statements)
references
References 55 publications
(66 reference statements)
16
232
1
1
Order By: Relevance
“…LNK is a negative regulator of thrombopoietinFthrombopoietin receptor (MPL)-mediated JAK2 activation; LNK-deficient mice exhibit increased number of megakaryocytes with increased ploidy, 5 increased number of erythrocyte progenitors, 6 as well as an expanded hematopoietic stem cell pool with enhanced self renewal. 7 LNK has been shown to down regulate signaling downstream of MPLW515L and JAK2V617F in vitro. 8,9 Indeed, in a transduction-transplant murine model, LNK deficiency accelerates and exacerbates MPN development induced by TEL-JAK2 and JAK2V617F.…”
Section: Introductionmentioning
confidence: 99%
“…LNK is a negative regulator of thrombopoietinFthrombopoietin receptor (MPL)-mediated JAK2 activation; LNK-deficient mice exhibit increased number of megakaryocytes with increased ploidy, 5 increased number of erythrocyte progenitors, 6 as well as an expanded hematopoietic stem cell pool with enhanced self renewal. 7 LNK has been shown to down regulate signaling downstream of MPLW515L and JAK2V617F in vitro. 8,9 Indeed, in a transduction-transplant murine model, LNK deficiency accelerates and exacerbates MPN development induced by TEL-JAK2 and JAK2V617F.…”
Section: Introductionmentioning
confidence: 99%
“…Lnk is an adaptor protein expressed in KSL cells and believed to negatively regulate the key signaling pathways for the proliferation of KSL cells such as stem cell factor (SCF) signaling and thrombopoietin signaling [10][11][12]. In Lnk-deficient mice, the proliferation of KSL cells is upregulated and the number of KSL cells in bone marrow is increased compared to that in wild-type mice [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Lnk-deficient HSCs show higher levels of symmetric proliferation in response to thrombopoietin (TPO) in ex vivo culture than wildtype HSCs (Seita et al, 2007). Biochemical analyses revealed that Lnk directly binds to phosphorylated tyrosine residues in JAK2 after TPO stimulation (Bersenev et al, 2008). Therefore, Lnk is a physiologic negative regulator of JAK2 in HSCs, and TPO/cMpl/JAK2/Lnk constitute a major regulatory pathway controlling HSC quiescence and selfrenewal.…”
Section: Lnkmentioning
confidence: 99%